Bilateral Double Maxillary Paramolars: A Rare Case Report - Aydin Ozkan; Hakan Dag; Hasan Ayberk Altug; Metin Sencimen (Journal of Clinical and Diagnostic Research, 2017)
Paramolars are rare supernumerary molars occurring buccally or lingually/palatally near the molar row. They may cause complications such as caries, periodontal disease and delay or prevention eruption of permanent teeth. Reports of bilateral entity are rarely found in the dental literature. The present article reports a rare case of bilateral double paramolars in the maxillary molar region in 21- year-old male patient.